The diagnostic significance of CDH17-positive circulating tumor cells in patients with colorectal cancer. (1st February 2023) - Pei, Xiao Meng; Wong, Heong Ting; Ng, Simon Siu Man; Leung, Wing Wa; Wong, Yee Ni; Tsang, Hin Fung; Chan, Amanda Kit Ching; Wong, Yin Kwan Evelyn; Yu, Allen Chi Shing; Yim, Aldrin Kay Yuen; Cho, William Chi Shing; Chan, John Kwok Cheung; et al.
ABSTRACT: Background: Colorectal cancer (CRC) is the second leading cause of cancer deaths in Hong Kong. We tested the hypothesis that circulating tumor cell (CTC) analysis by ARB101 antibody could be used as a tool for CRC detection, progression, and therapy response. Research Methods: ARB101 antibody was used for investigation of CDH17 expression in formalin-fixed, paraffin-embedded (FFPE) tissue sections and circulating tumor cells (CTCs) of CRC patients. Results: Using ARB101, highest sensitivity was observed in 98/100 (98%) colorectal cancer tissue compared to 72/100 gastric cancer (72%) and 27/32 pancreatic cancer (84%). Immunoreactivity of CDH17 was significantly higher in distant metastatic (tumor-node-metastasis [TNM] stage IV) than non-distant metastatic (TNM stage I to III) CRC. ARB101 antibody also manifested the higher sensitivity than c-erbB2 (8%) and epidermal growth factor receptor (EGFR)-targeting antibodies (37%) with the significance (p < 0.0001). ARB101 positive CTCs were detected in 64/83 (77%) TNM stage I to IV CRC patients. Furthermore, ARB101 positive CTCs detected in TNM stage I to III CRC patients before and after surgical operation are statistically significant (p < 0.0001). Conclusions: CTC detection by ARB101 antibody could serve as a potential non-invasive approach for CRC detection, progression, and monitoring of treatment response.